Stability analysis of solutions to an optimal control problem associated with a Goursat-Darboux problem - Idczak, Dariusz; Majewski, Marek; Walczak, Stanisław (Zielona Góra: Uniwersytet Zielonogórski)
In the present paper, some results concerning the continuous dependence of optimal solutions and optimal values on data for an optimal control problem associated with a Goursat-Darboux problem and an integral cost functional are derived.
Keywords: Goursat-Darboux problem; optimal control; continuous dependence